Fungal transformation and reduction of phytotoxicity of grape pomace waste. (December 2019) - Troncozo, María I.; Lješević, Marija; Beškoski, Vladimir P.; Anđelković, Boban; Balatti, Pedro A.; Saparrat, Mario C.N.
Abstract: Grape pomace (GP) from Vitis labrusca, the main byproduct from "American table wine" production, is recalcitrant to degradation, and its accumulation is a serious problem with negative environmental impacts. In this work, transformation of grape pomace using a steam pretreatment followed by incubation of GP during a 90-day period with six different fungi were evaluated. Several fungi tested reduced the phytotoxicity of water-soluble fraction (WSFd ) from steam-pretreated GP after 90 days' incubation to lettuce and tomato seeds. U. botrytis caused the largest effective phytotoxicity reduction of WSFd (used in the concentration range of 10–1.25% p/v) and was the only fungus causing the removal of monoaromatic compounds. Therefore, this procedure with U. botrytis effectively reduces the availability of phytotoxic monoaromatic compounds in GP, which opens a way for the development of guidelines for the management of these wastes and their potential use as organic amendments in agricultural soil. Highlights: Grape pomace is a source of phytotoxic monoaromatic compounds. Ulocladium botrytis LPSC 813 can grow on steam-pretreated grape pomace. Ulocladium botrytis LPSC 813 removes phytotoxic monoaromatic compounds. Ulocladium botrytis LPSC 813 causes effective phytotoxicity reduction of grape pomace. Phytotoxicity reduction was confirmed on lettuce and tomato seeds.